The past, Present and Future of Parliamentary and Legislative Studies. Issue 4 (20th April 2022) - Bhattacharya, Caroline; Hart, Gavin; Haughey, Sean; Holden Bates, Stephen; Meakin, Alexandra
Abstract: This special section emanates from the roundtable on the past, present and future of parliamentary and legislative studies, held as part of the PSA Parliaments specialist group's 2020 annual conference.